Psychiatric symptoms in individuals who use ketamine versus methamphetamine—implications for glutamatergic and dopaminergic model for schizophrenia: a cohort study. (October 2016) - Liao, Yanhui; Qi, Chang; Wu, Qiuxia; Tang, Jinsong
Abstract: Background: Both ketamine and methamphetamine have been used for studying the positive, negative, and cognitive symptoms, and dopaminergic and GABAergic dysfunction observed in acute schizophrenia. We aimed to explore and compare the prevalence and factor structure of psychotic symptoms in chronic ketamine and methamphetamine users. Methods: We recruited chronic ketamine and methamphetamine users from the Guangzhou Baiyun and Kangda voluntary drug rehabilitation centres in the Hunan Province, China. All these participants met the Diagnostic and Statistical Manual of Mental Disorders, fourth edition criteria for lifetime ketamine or methamphetamine dependence determined from the Structured Clinical Interview. Participants were excluded if they met criteria for other substance dependence (excluding nicotine) at any time. All participants gave a full history of psychiatric symptoms. We used The Positive and Negative Syndrome Scale (PANSS) to assess the psychotic symptoms in these two groups. Independent sample t -tests or χ 2 -square test were done to determine group differences. The protocol was approved by the university ethics committee (S163, 2011). Findings: We recruited 344 chronic ketamine users (34 were female; mean age 26·8 years, SD 5·43; mean years of education 11·6 years, SD 2·45) and 456 chronic methamphetamine users (28 were female; mean age 29·3 years SD 6·33, mean years of education 11·1 years, SD 2·78) between Jan 1, 2012, to Dec 31, 2015. 183 (53%) of 344 ketamine users and 375 (82%) of 456 methamphetamine users (χ 2 t=78·37, p<0·0001) had psychiatric symptoms, with a mean duration of 23·5 months (SD 24·58) for ketamine users and 15·0 months (SD 19·42) for methamphetamine users (t=4·05, p<0·0001). The mean age when first having psychotic symptoms was 25·4 years (SD 5·55) in ketamine users and 28·5 years (6·33) in methamphetamine users (t=–5·84, p<0·0001). Mean scores on PANSS TOTAL were 52·6 (SD 23·34) in ketamine users and 61·7 (29·61) in methamphetamine users (t=–4·84, p<0·0001). Mean scores for ketamine and methamphetamine use groups on positive, negative, and general subscales were 10·8 (SD 5·45) versus 15·0 (8·26; t=–8·80, p<0·0001), 12·2 (6·91) versus 14·5 (8·68; t=–4·07, p<0·0001), and 29·7 (12·98) versus 32·2 (15·22; t=–2·55, p=0·011), respectively. Interpretation: This study provides first evidence for comparing psychotic symptoms in chronic ketamine and chronic methamphetamine users. The findings suggest that chronic methamphetamine users have higher risk of suffering from psychiatric symptoms and more severity of chronic drug-induced schizophrenia-like symptoms than do chronic ketamine users. These findings might provide some implications for pharmacological (glutamatergic and dopaminergic) models of schizophrenia. Funding: Natural Science Foundation of China (81100996 to YL, and 81371480 to JT). The funder of the study had no role in study design, data collection, data analysis, data interpretation, or writing of the report. The corresponding authors had full access to all the data in the study and had final responsibility for the decision to submit for publication.